(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Fistula-in-ano is troublesome problem encountered in general practice. It consists of 1.6% of all surgical admissions and leads to physical, psychological and social problems. The management consists of multiple modalities with varied results. Present study evaluates medicated seton (Ksharsutra) as a minimal invasive modality of treatment. Methodology: The study was randomized control trial carried out at tertiary care hospital with an aim to assess the efficacy of Ksharsutra Vs fistulectomy. The subjects were clinically diagnosed and MRI confirmed cases of low fistula-in-ano. They were block randomized into two interventional groups. Study group were subjected to introduction of Ksharsutra under local anesthesia while control group under saddle block had a formal fistulectomy done. The outcome measures were wound healing time, hospital stay and recurrence. Results: A total of 63 patients were evaluated of which 33 were allocated to Ksharsutra group and 30 patients underwent fistulectomy. The male: female ratio was 8:1 and mean age of the patients was 38.4 years SD ± 11.03. Perianal sinus with or without pain and discharge was presenting complaints in all patients.1/3rd patient gave history of past incision and drainage while 2/3rd patients had spontaneous rupture. Majority (76%) fistulae were intersphincteric and rest were transsphincteric. The mean healing duration was 5.5 weeks in fistulectomy and 6 weeks in Ksharsutra (p>0.1 [NS]). Recurrence rate and incontinence rates were also significantly not different. Conclusion: The equivalence of results of Ksharsutra with traditional fistulectomy made it an alternative minimal invasive modality of treatment which can be offered on outpatient basis.